A Lack of Significant Effect of POR*28 Allelic Variant on Tacrolimus Exposure in Kidney Transplant Recipients. Issue 2 (April 2016) - Jannot, Anne-Sophie; Vuillemin, Xavier; Etienne, Isabelle; Buchler, Mathias; Hurault de Ligny, Bruno; Choukroun, Gabriel; Colosio, Charlotte; Thierry, Antoine; Vigneau, Cécile; Moulin, Bruno; Rerolle, Jean-Philippe; Heng, Anne-Elizabeth; et al.
Abstract : Background: POR*28 is a recently newly described allelic variant of the cytochrome P450 oxidoreductase (POR), which might be associated with an increased metabolic activity of P450 cytochromes (CYP) 3A5 and 3A4. Consequently, carriers of at least 1 allele of this polymorphism could require increased calcineurin inhibitors doses to reach the target residual concentrations (C0). The objective of this study was to test whether the allelic variant of POR, which is associated with an increased metabolic activity of CYP3A, impacts tacrolimus (Tac) pharmacokinetics. Methods: We tested this hypothesis in a population of 229 kidney transplant recipients (KTR) from a large, multicenter, prospective and randomized study. We have analyzed the association between POR*28 genotype and the proportion of individuals reaching the target Tac residual concentration (Tac C0) 10 days after transplantation. We have also measured the association between POR*28 and the Tac C0, and adjusted Tac C0 (Tac C0/Tac dose) over time using generalized mixed linear models. Results: Ten days after transplantation, there was no difference of frequencies of KTR within the target range of Tac C0 (C0 10–15 ng/mL) according to the POR*28 genotype ( P = 0.8). The mean Tac C0 at day 10 in the POR*1/*1 group was 15.3 ± 9.7 ng/mL compared with 15.7 ± 7.8 ng/mL in the POR*1/*28 group and 14.2 ± 6.8 ng/mL, in the POR*28/*28 group, P = 0.8. The adjusted Tac C0 was not associated with POR*28 genotype over time (random effects model, P = 0.9). When restricted to KTR expressing CYP3A5, POR*28 genotype did not impact the proportion of individuals within the Tac C0 target range neither the adjusted Tac C0 (random effects model, P = 0.1). Conclusions: POR*28 does not significantly influence Tac pharmacokinetic parameters in a large cohort of KTR. This study does not confirm recent findings indicating that POR*28 carriers require more Tac to reach target C0.